Instant messenger smartphone application for endosonographer/cytopathologist real-time interaction at a distance in EUS-FNA for solid pancreatic lesions - Machado, Rodrigo S.; Richa, Rafaela; Callegari, Fabiano; Souza, Giovana B.; Tolentino, Luciano L.; Nakao, Frank S.; Ferrari, Angelo, Jr.; Libera, Ermelino (Endoscopy International Open, 2019)
Background and study aims Telecytopathology (TCP) may allow proper and timely evaluation of endoscopic ultrasound-guided fine-needle aspiration (EUS-FNA) specimens. The aim of this study was to evaluate the feasibility of TC through a multiplatform instant messenger smartphone application to evaluate specimens of EUS-FNA of pancreatic solid lesions.Patients and methods Twenty-three patients (14 male/9 female; median age: 56 yr.; age range: 33 – 86) with a solid pancreatic lesion were included. Exclusion criteria were as follows: age < 18 yr and predominantly cystic lesions. During each EUS-FNA, after each pass, the aspirated material was spread over a glass slide and was stained by the endoscopist. The glass slide was then reviewed on a microscope with a smartphone fitted in, and the most representative fields were captured and sent to the cytopathologist using WhatsApp Messenger.Results In initial evaluation using TCP rapid on-site evaluation (ROSE), adequate cellularity of the glass slide was detected in 16 of 23 patients (69.6 %). An initial diagnosis of malignancy (positive or suspicious) was possible in 14 of 23 patients (60.8 %).Conclusion The current study demonstrated the feasibility of a low-cost, Internet-based, telecytopathology system using WhatsApp Messenger to provide ROSE of EUS-FNA slides in patients with solid pancreatic lesions.